«The Maternal is Political»: Exploring Mothering among Women with Disability - Pinto,Paula Campos (2011)
In this paper disabled women's mothering experiences in the Portuguese society are explored, drawing from in-depth interviews with 21 women with a variety of impairments, living in the metropolitan region of Lisbon. The women offer accounts of mothering which in many ways resonate with the findings reported in the mainstream literature on care, motherhood, and mothering. But disability is also a factor of difference in their lives that transforms and re-shapes their experiences and practices of mothering. Thus, both commonality and difference permeate their stories. Importantly too, women's narratives highlight their self-determination in the face of stigmatizing discourses which historically have operated to exclude many like them from motherhood. Thus for these women, mothering is also a site of struggle and empowerment. For them the maternal is political.